Cataract surgery under topical anesthesia using 2% lignocaine jelly and intracameral lignocaine: Is manual small incision cataract surgery comparable to clear corneal phacoemulsification? - Gupta Sanjiv; Kumar Ajai; Agarwal Swati (Indian Journal of Ophthalmology, 2010)
A prospective comparative study was undertaken to compare the patients′ pain experience, surgical outcome and surgeon′s experience in phacoemulsification and manual small incision cataract surgery (MSICS) under topical anesthesia supplemented with intracameral lignocaine (TASIL). In Group 1 (n=88) phacoemulsification was done and in Group 2 (n=92) MSICS was done. Pain scores were marked by the patients on a Visual analog scale (VAS) after the surgery. The surgical experience was noted on a questionnaire by the operating surgeon. Descriptive analysis and one-tailed Mann-Whitney test were used to draw results. The average VAS score in Group 1 was 0.65 (SD 1.31) and in Group 2 it was 0.90 (SD 1.22). This difference in the average was not statistically significant with P=0.09. The study demonstrates that MSICS and phacoemulsification both can be done safely under TASIL with acceptable patient comfort, and the pain experienced by the patients during the procedures is comparable.